Can crop yield risk be globally diversified? - Xiaoliang Liu; Wei Xu; Martin Odening (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
In 2007 and 2008 world food markets observed a significant price boom. Crop failures simultaneously occurring in some of the world's major production regions have been quoted as one factor among others for the price boom. Against this background, we analyse the stochasticity of crop yields in major production areas. The analysis is exemplified for wheat, which is one of the most important crops worldwide. Particular attention is given to the stochastic dependence of yields in different regions. Thereby we address the question of whether local fluctuations of yields can be smoothed by international agricultural trade, i.e. by global diversification. The analysis is based on the copula approach, which requires less restrictive assumptions compared with linear correlations. The use of copulas allows for a more reliable estimation of extreme yield shortfalls, which are of particular interest in this application. Our calculations reveal that a production shortfall, such as in 2007, is not a once in a lifetime event. Instead, from a statistical point of view, similar production conditions will occur every 15 years.
Keywords: C14; Q19; 330; crop yield risk; fully nested hierarchical Archimedean copulas (FNAC); price boom; Weizenpreis; Rendite; Kopula (Mathematik); Agraraußenhandel; Portfolio-Management; Theorie; Welt